STRATEGI DAN UPAYA PENGEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) - Imran Ukkas (Universitas Muhammadiyah Makassar, 2017)
As one of the best destinations of tourist in Palopo City, Village Latuppa provides a number of very promising business potential. But this business opportunity can’t be fully utilized by the people of Latuppa and the perpetrators of UMKM. Therefore, this program aims to provide knowledge and understanding of the management and development UMKM professionally and independently in order to support the income and improve people's welfare in Village Latuppa. The implementation methods used are entrepreneurship seminar and business practices. First of all, the people of Latuppa will be given a concept to manage the business professionally, innovatively, creatively and independently through entrepreneurship seminar. Furthermore, people of Latuppa will be led to practice the manufacture of spinach chips and hanging lanterns. So, it can be concluded that the implementation of these activities have a positive effect to the people of Latuppa to improve business potential especially in the sector of UMKM. In the end this program can support the income and improve the welfare of the people of Latuppa and also contribute to improving economic growth in Palopo